When Traceurs Meet Steel. Re-signification of a "Functional" Material within the Practice of Parkour - Santori , Valerio (E|C, 2023)
Exalted by the modernist discourse due to physical properties such as hardness and tensile strength, steel within the practice of parkour seems to possess entirely different, even opposing, characteristics. In this paper, this “schizophrenia of steel” is investigated by drawing on recent insights by Cosimo Caputo on the concept of “double materiality” in Hjelmslev, which opens the doors to the recognition of a multiplicity of substances. The proposed hypothesis posits that the affordances of a particular material should be understood as possibilities of reacting to a non-hypothetical resistance, that is, not subjected to analysis, and that such an approach reveals the perpetual ambiguity of the “contract between man and material”, as formulated by Hammad.